Job Insecurity and Turnover Intentions among Banking Sector Employees: The Moderating Role of Organizational Support and Ethical Leadership - Addai, Prince; Mottey, Rejoice; Afrifah, Michelle; Osei Boakye, Augustine (SEISENSE (PRIVATE) LIMITED, 2022)
Purpose - Job insecurity exerts a significant impact on turnover intentions among employees. The association may be partly due to the influence of organizational support and the ethicality of leaders. However, there is a shortage of studies on the ameliorating role of organizational support and ethical leadership in the nexus between job insecurity and turnover intentions. Thus, the purpose of this study is to examine the nexus between job insecurity and turnover intentions among banking sector employees. The moderating role of organizational support and ethical leadership on the underlying relationship was assessed to achieve this. Design/methodology/approach – One hundred and sixty (160) banking sector employees were conveniently selected to participate in the study. The sample consisted of female (n = 92) and male (n = 68) employees, ranging from 23 to 49 years. Standardized measures were used in soliciting respondents' demographic characteristics, perceived job insecurity, ethical leadership, organizational support, and turnover intentions. Data were analyzed using regression analysis. Findings – Results revealed a significant positive correlation between perceived job insecurity and turnover intentions. Organizational support and ethical leadership also moderated the association between job insecurity and turnover intentions. The influence of job insecurity on turnover intentions minimizes when management provides the needed support and favorable climatic conditions. Originality/value – In general, the study highlights the importance of organizational support and ethical leadership in lessening the impact of job insecurity on turnover intentions.